Association of hypovitaminosis D with sleep parameters in rotating shift worker drivers. - Menezes Júnior, Luiz Antônio Alves de (2023)
Objective To evaluate the association between sleep parameters and hypovitaminosis D in rotating shift drivers. Material and Methods We conducted a cross-sectional study on 82 male rotating shift workers (24–57 years old) with at least one cardiovascular risk factor (such as hyperglycemia, dyslipidemia, abdominal obesity, physical inactivity, hypertension, and smoking). Polysomnography was used to evaluate sleep parameters. Logistic regression was used to model the association between hypovitaminosis D and sleep parameters after adjustment for relevant covariates. Results Hypovitaminosis D (< 20 ng/mL) was seen in 30.5% of the workers. Shift workers with hypovitaminosis D had lower sleep efficiency (odds ratio [OR]: 3.68; 95% confidence interval [CI]: 1.95–5.53), lower arterial oxygen saturation (OR: 5.35; 95% CI: 3.37–6.12), and increased microarousal index (OR: 3.85; 95% CI: 1.26–5.63) after adjusting. Conclusion We suggest that hypovitaminosis D is associated with greater sleep disturbances in rotating shift workers.